Teacher-Student Relationship in Homoeopathic Institutions An Invincible Bondage (Homoeopathy for All, 2023)
Aristotle, the famous ancient  Greek philosopher, has rightly  said, “Educating the mind without  educating the heart is no education  at all.” This means, the teachers  should teach their students not  mechanically, nor merely as a part  of their duties because they are paid  for this, but they should be heartily  involved while teaching their  students. It is an undeniable fact  that the students pay more respect to  their teachers, than anyone else. So,  the love and affection with which  the teachers teach in the classrooms  have lasting effects in the minds  of their disciples, even outside the  boundaries of their classrooms. Our  society keeps the teachers in high  esteem, pays immense respect to  them because they know that the  latter have a vital role in not only  building up the future careers of their  siblings, but also their character,  morale, behaviour, domestic and  social relationships, and above  all, for transforming them to good  human beings blended with humane  attitude and compassion.
Keywords: philosopher; boundaries; morale; behaviour